Triple Combination Therapy for Hepatitis C with Telaprevir Exhibits Greater Early Antiviral Activity than with Boceprevir. Issue 5 (July 2013) - Benito, José M; Sánchez-Parra, Clara; Maida, Ivana; Aguilera, Antonio; Rallón, Norma I; Rick, Fernanda; Labarga, Pablo; Fernández-Montero, José V; Barreiro, Pablo; Soriano, Vincent
Background: Achievement of early viral suppression is important in patients with chronic HCV infection treated with telaprevir (TLV) or boceprevir (BOC) to avoid selection of drug resistance and attain cure. No head-to-head studies comparing TLV and BOC have been performed so far. Methods: All consecutive individuals who initiated triple HCV therapy with TLV or BOC outside clinical trials at three European clinics were evaluated. Rapid virological response (RVR) was defined as unquantifiable HCV RNA (<25 IU/ml) at week 4 for TLV and at week 8 for BOC (4 weeks after lead-in). Results: A total of 106 patients were evaluated, 33 treated with BOC and 73 with TLV. Median age, gender, body mass index, baseline HCV RNA, HCV subtype 1a (45% versus 42%) and IL28B-CC alleles (29% versus 23%) did not differ significantly in BOC and TLV groups, respectively. HIV coinfection was more prevalent in patients on TLV than BOC (24% versus 44%). Conversely, more patients on BOC than TLV had previously failed pegylated interferon plus ribavirin (82% versus 64%). RVR was achieved by 82% of patients on TLV versus 59% on BOC ( P =0.001). Multivariate logistic regression analysis confirmed that TLV use was the strongest predictor of RVR (OR 3.54 [95% CI 1.23, 10.24]; P =0.02), others being HCV subtype 1b versus 1a (OR 3.26 [95% CI 1.17, 9.09]; P =0.02) and low baseline HCV RNA (OR 0.41 [95% CI 0.16, 1.03]; P =0.06). Prior interferon exposure, HIV coinfection or absence of advanced liver fibrosis did not influence the likelihood of RVR. Conclusions: Compared to BOC, triple therapy with TLV produces greater RVR rates. TLV might be a better option in more difficult-to-cure patients, such as those with high baseline HCV RNA and/or HCV 1a subtype. HIV coinfection does not influence early HCV RNA responses.